An Arctic sea ice spring bloom driven and dominated by Dinoflagellates - a harbinger of the future sea ice? - Lund-Hansen, Lars Chresten; Kobberup, Emil; Jensen, Lasse Z.; Sorrell, Brian; Søgaard, Dorte Haubjerg (Frontiers in Marine Science, 2024)
The sea ice spring bloom is essential for Arctic marine food webs, and the sea ice algae are one of the main carbon sources to higher trophic levels. Contrary to the general succession in sea ice where spring blooms are typically dominated by diatom species, we here report a spring bloom driven by dinoflagellates. Redundancy analysis showed that main drivers of the dinoflagellate bloom were high irradiances at the top of the ice core and high nutrient availability, combined with warm ice conditions. These results suggest that an overall climate-driven decline in snow cover on sea ice, more open leads and thinner sea ice may promote blooming of dinoflagellates over diatoms. This dinoflagellate alternative to a bloom of diatoms might have important ecological consequences, as dinoflagellates are richer in omega-3 fatty acids, with important implications for the Arctic marine food web and thereby transport of energy to higher trophic levels. The dinoflagellates Polarella glacialis and Chytridinium, an ectoparasit on copepod eggs, and the green algae Ulothrix were present in the sea ice in relatively high abundances.